Comparing The Effect Between Energy Reducing Diet And Food Combining On Body Weight Change Among Overweight Adult - Didit Damayanti; Pritasari Pritasari; Nanang Prayitno; Iskari Ngadiarti; Nils Aria Zulfianto (Politeknik Kesehatan Kemenkes Jakarta II, 2020)
Few years ago, food combining a popular weight reducing diet has been promoted and practiced by the public in Indonesia. The objective of this study was to compare the effect of food combining on change in body weight with a calorie reducing diet. We used a crossover experiment study design where 12 healthy free-living subjects (10 women, 2 men), age range 18-21 years old and BMI > 25 kg/m2 were randomly allocated into each groups. Participants were prescribed two diets for 3 consecutive weeks with a 6 week washout period when subjects were instructed free to eat. Diet of 1200 kcal/day for women and 1500 kcal/day for men were prescribed for respondents, whereas the food combining intervention included fruits in the morning and a combination of protein foods with vegetables or carbohydrate foods and vegetables for the other meals. The body weight and nutrients intake were measured before and after each intervention. The result analyzed using a linear mixed model and it showed there was no significant difference (p=0.235) in change in body weight after treatment with the food combining (65.8 kg, CI 95%: 59.7, 71.8) as compared to the calorie restricted diet (66.5 kg, CI: 95%: 60.4, 72.5) at F (1, 10) =1.59. The risk inadequate intake of protein, vitamin B-2, folate, calcium, iron and zinc after followed food combining compared to calorie restricted diet should taking into consideration. The food combining as well as energy reducing diet showed a similar effect on reduction in body weight.